INTERVENSI MBCT DALAM MENGATASI GANGGUAN KECEMASAN AKIBAT KECANDUAN MEDIA SOSIAL PADA GENERASI Z: LITERATUR REVIEW - Sholikha, Azmatun; Farhan, Muhammad Haikal; Rohim, Abdur; Utma, Putri Safaatul; Nurullida, Alya Sakila; Muna, Naeila Rifatil (Jurnal Konseling dan Psikologi Indonesia, 2025)
The massive use of social media by Generation Z has a significant impact on their mental health, particularly in triggering anxiety disorders. Generation Z, born and raised in the digital era, has a high level of attachment to social media, which is often used compulsively as a means of escape, a pursuit of social validation, and due to the addictive design of these platforms. This dependency can lead to various forms of anxiety disorders, such as social anxiety, generalized anxiety disorder, and panic attacks. This study aims to examine the effectiveness of Mindfulness-Based Cognitive Therapy (MBCT) in addressing anxiety disorders caused by social media addiction among Generation Z through a literature review approach. The findings indicate that MBCT, which combines mindfulness and cognitive therapy, is effective in reducing anxiety symptoms, improving emotional regulation, and enhancing self-awareness among adolescents. The MBCT intervention is conducted over eight sessions, incorporating techniques such as breath meditation, thought observation, identification of negative thinking patterns, and strengthening awareness of emotional experiences. Literature findings suggest that MBCT is not only effective in clinical settings but can also be flexibly applied in educational environments and digital communities, making it a potential preventive and curative strategy for tackling the mental health crisis in the digital era. The success of this intervention is supported by active participant engagement as well as contextual support from trained facilitators and social environments aligned with Generation Z’s characteristics.